2011
DOI: 10.4103/0189-6725.91673
|View full text |Cite
|
Sign up to set email alerts
|

Comparing caudal and penile nerve blockade using bupivacaine in hypospadias repair surgeries in children

Abstract: Without ultrasonography and with blind block, with anatomic landmarks only, the caudal block success rate is high and if there is no contraindication for caudal block, it is the best choice in children under 6 years old (or 25 kg) for hypospadias repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…They found that the difference of post-operative pain between the two groups was insignificant for 2 hours then there was decrease in FLACC pain score in caudal group after 2 hours when compared to penile group, they concluded that the duration of post-operative analgesia was more in caudal group than that of DPNB also the supplementary analgesic need was minimized with insignificant incidence of complication in both groups. In addition, Mahin et al, [12] who aimed to compare caudal and penile nerve block using bupivacaine in post-operative pain control in hypospadias repair in children. They demonstrated that, caudal block has more success rate and more quality also longer duration of postoperative analgesia when compared to penile block.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the difference of post-operative pain between the two groups was insignificant for 2 hours then there was decrease in FLACC pain score in caudal group after 2 hours when compared to penile group, they concluded that the duration of post-operative analgesia was more in caudal group than that of DPNB also the supplementary analgesic need was minimized with insignificant incidence of complication in both groups. In addition, Mahin et al, [12] who aimed to compare caudal and penile nerve block using bupivacaine in post-operative pain control in hypospadias repair in children. They demonstrated that, caudal block has more success rate and more quality also longer duration of postoperative analgesia when compared to penile block.…”
Section: Discussionmentioning
confidence: 99%
“…compared caudal block and dorsal penile block with bupivacaine and reported a failure rate of 1.7% in the caudal group and 2% in the penile group. In another study by Azerfarin et al using bupivacaine, additional analgesia was required by 1 (2.3%) patient in the caudal group, and 3 patients (7.4%) in the penile group and these patients were evaluated as failed block 16 . In our study, opioid was used as an additional analgesic in 8% of the patients undergoing caudal block, and in 8.3% of patients with dorsal penile block in the intraoperative period or in the recovery room and these blocks were considered to be failures.…”
Section: Discussionmentioning
confidence: 99%
“…We performed network meta-analysis by using RevMan 5.4 and Stata 16.0 software. Initially, the event with a zero number 15,25 was recti ed to ensure the thorough completion of the data preprocessing stage. The study yielded dichotomous outcomes, for which odds ratios (ORs) and 95% con dence intervals (95% CIs) were computed.…”
Section: Satistical Analysismentioning
confidence: 99%